Anancy: entre telas de araña y carnaval - Pochet Rodríguez, Lina (2012)
This work presents a reading of the tales of Anancy, applying some of the elements of carnival Batjin to determine how they violate the social order. Therefore, the proposal bajtniana is very useful for analyzing your answer and try to show how Anancy tales interweave and its protagonist's transgression of the established order